RAIN FORECAST FOR HO CHI MINH CITY USING DOPPLER WEATHER RADAR DWRS-2500C - Dung, Dang Quoc (GeoScience Engineering, 2016)
Rainfall quantity is randomly variating over space and time. Monitoring and forecasting of rainfall is a difficult task, especially for short-term period from 30 minutes – 3 hours. Recently one of the new solutions in short term forecasting of severe rain or storm is using Doppler weather radar. This research presents some results of forecasting the wind direction and velocity of a typical rainy day, September 14, 2010, based on CAPPI images of DWRS-2500C radar in Nha Be district, HCM City. The results showed that the Doppler radar, in a scanning radius of 30km, is very effective in forecast of severe rainfall for each region and district when reflected radar signals from clouds moving towards the city are detected. This research will provide useful information in the forecast of severe rain for flood prevention works in HCM City.